If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(y + 2) = 48 Reorder the terms: y(2 + y) = 48 (2 * y + y * y) = 48 (2y + y2) = 48 Solving 2y + y2 = 48 Solving for variable 'y'. Reorder the terms: -48 + 2y + y2 = 48 + -48 Combine like terms: 48 + -48 = 0 -48 + 2y + y2 = 0 Factor a trinomial. (-8 + -1y)(6 + -1y) = 0Subproblem 1
Set the factor '(-8 + -1y)' equal to zero and attempt to solve: Simplifying -8 + -1y = 0 Solving -8 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1y = 0 + 8 -1y = 0 + 8 Combine like terms: 0 + 8 = 8 -1y = 8 Divide each side by '-1'. y = -8 Simplifying y = -8Subproblem 2
Set the factor '(6 + -1y)' equal to zero and attempt to solve: Simplifying 6 + -1y = 0 Solving 6 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 0 + -6 -1y = 0 + -6 Combine like terms: 0 + -6 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6Solution
y = {-8, 6}
| 7z=8z^2 | | -0.7x+8.45=-0.3x+7.25 | | y(y-7)=44 | | -2v+8=-4v+4 | | 3x-6x-15=27 | | 4/5x2-6/y | | .16y+.16=.125y+.8 | | 2(3x+7)=-6+2 | | -11m=-99 | | y(y-3)=-2 | | -11m=99 | | 7z=8Z*2 | | y(y+8)=65 | | (4-2x)/5+3=9 | | -0.1x+0.4x-8=-2 | | 750=20d | | 12x-42=8x-18 | | 10z-19-3z+5=0 | | 65t=130(t-3) | | (11x+2)/6=4 | | x/8-4=-6 | | 11x+2/6=4 | | 2-x-2/5y=0 | | 2x-5+29=180 | | Isy=x+2linear | | 2x-5+29=90 | | -x+9=-29 | | -x-10+4x=11 | | 30+x/2-25=43 | | 6x-10=5(x+3) | | 40(t)=-16(t^2)+40t+10 | | 2.7v-1.2=4.5v+2.4 |